Preventing and managing computer related injuries - Kantola Productions, Stanford Center for Research in Disease Prevention (Mill Valley, CA: Kantola Production, 2001., 2022)
The experts at Stanford pinpoint the causes and explain the cures for computer-related traumas. Following these ergonomic principles will minimize aches and strains and increase productivity